High performance sport programs and emplaced performance capital in elite athletes from developing nations - Riot, C.; O`Brien, W.; Minahan, C. (Sport Management Review, 2020)
• Emplaced performance capital examines the material and sensory world of elite athletes. • The material and sensory produce affects and capacities impacting athlete`s development. • Deficits of emplaced performance capital affect athlete`s performance at international events. • Sports managers need to be attuned to the affects produced through the material and sensory.